Hamric and hanson's advanced practice nursing : an integrative approach - Tracy, Mary Fran; O'Grady, Eileen T.; Phillips, Susanne J. (St. Louis, Missouri : Elsevier, 2023)
"The purpose of this book is to continue to promote the clarion call for nursing leaders, educators, and practicing clinicians to seek integrated understanding of APRNs"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Nurse practitioners